Accuracy of fine needle aspiration cytology in the diagnosis of palpable head and neck masses in a tertiary health care center - Swamy, GG; Singh, A; Ahuja, JM; Satyanarayana, N (Journal of College of Medical Sciences-Nepal, 2012)
Palpable masses in head and neck are a common clinical finding, affecting all age groups. These lumps may be extremely worrying for both physician and patient, as a wide variety of pathological conditions. Accurate cytological analysis has played a major role in evaluation and planning for surgery. We attempted to evaluate the role of Fine Needle Aspiration Cytology (FNAC) in diagnosing lesions of the head and neck region and to review the diversity of lesions in the patients attending the hospital. The study was conducted retrospectively in the department of pathology at College of Medical Sciences- Teaching Hospital, Bharatpur, Nepal a tertiary health care centre. The target population comprised patients presenting with palpable masses at head and neck region during the period of February 2007 to December 2009. The accuracy of FNAC was verified by histological examination in this final study group of (n=125) patients. In these (n=125) patients, twenty five were males and hundred were females. Thyroid gland (60%) was the commonest site aspirated, followed by lymph node (20%), salivary gland (16%) and soft tissue lesions (4%). In our study the sensitivity was 87.5%, the specificity was 100%, the positive predictive value was 100%, the negative predictive value was 98.26% and false negatives were 12.5%. We concluded that FNAC is a safe, cost-effective, sensitive and specific technique in the initial evaluation of head and neck masses. A correct cytological diagnosis can be achieved in a majority of cases, avoiding the need for surgical interventions. Journal of College of Medical Sciences-Nepal,2011,Vol-6,No-4, 19-25 DOI: http://dx.doi.org/10.3126/jcmsn.v6i4.6721